To Speak as a Judge: Difference, Voice and Power by Sandra Berns - Petersson, Sandra (Victoria University of Wellington Law Review, 2001)
This article is a book review of Sandra Berns To Speak as Judge: Difference, Voice and Power (Ashgate, Aldershot (UK), 1999) 241 + viii pages, 180. According to Petersson, the book is a postmodern feminist exploration of the nature of adjudication and offers an observational account of judging focussed on the level of superior courts. The central theme of the book is the position of women judges and of what it means to be a woman and to speak as a judge, and to speak as a woman in a world in which woman remains a negation.